Barriers and facilitators to contraception provision among rural healthcare providers - Alexandra Buscaglia; Annie Glover; Nicole Smith; Al Garnsey (Contraception and Reproductive Medicine)
Abstract Background Access to a full range of contraceptive options ensures that individuals can make autonomous decisions about their health and wellbeing. Contraceptive continuity requires that individuals have access in their local communities to a variety of methods, which may change throughout their reproductive lives. Individuals living in rural areas face healthcare access barriers which require special considerations to ensure continuous and effective utilization of contraception to support family planning decision-making. One particular type of family planning service—contraception provided to the postpartum individual—presents challenges related to reimbursement, provider training, and timing of placement, which can be complicated further for individuals who must travel for care. Objective This study sought to assess family planning provider perspectives in rural communities, including their knowledge, attitudes, and practices related to general contraception provision, provision of contraception in the specialized circumstance of the postpartum period, and provider assessment of barriers to care to identify strategies to improve access to contraception across the reproductive life cycle. Methods We conducted a mixed methods study with an electronic survey of 90 reproductive healthcare providers, and semi-structured follow-up interviews of 9 providers. All providers are currently licensed and provide patient care in Montana. The survey instrument was designed with feedback from physicians and nurses and included questions on contraceptive practices, knowledge, and barriers to providing contraceptive care. Quantitative survey results were analyzed using descriptive statistics and bivariate tests of significance. Qualitative interviews were coded using a combined inductive and deductive approach. Results Montana providers consistently reported cost and insurance-related procedural barriers. Additional important themes emerged from qualitative interviews regarding barriers to contraceptive access, including experiences with provider-, institutional-, and practice-level barriers, and provider philosophy and approach to contraceptive care. Conclusions This study identifies knowledge gaps, institutional and procedural barriers and facilitators, and provider approaches to contraceptive care in Montana. Findings suggest that the need to increase provider awareness of Montana Medicaid coverage of immediate postpartum contraception. Results should inform future interventions to increase access to hospital-based contraceptive care.